Drugs, Sex, and Condoms: Identification and Interpretation of Race‐Specific Cultural Messages Influencing Black Gay and Bisexual Young Men Living with HIV. Issue 3 (24th November 2016) - Harper, Gary W.; Tyler, April Timmons; Bruce, Douglas; Graham, Louis; Wade, Ryan M.; ,
Abstract: Black gay and bisexual young men carry a disproportionate burden of HIV in the United States. This study explored Black gay and bisexual young men living with HIV's identification and interpretation of race‐specific cultural messages regarding substance use, sexual activity, and condom use. A total of 36 Black gay and bisexual young men living with HIV (ages 16–24, mean = 20.6 years) from four geographically diverse regions of the United States participated in qualitative in‐depth interviews. Results from this study elucidate the ways in which these young men interpret various forms of race‐specific cultural messages and experiences regarding substance use, sexual activity, and condom use. Participants discussed cultural messages and experiences promoting and discouraging condoms and substance use. Regarding sexual activity, only messages and experiences promoting sex were reported. Across all three categories, messages and experiences promoting risk were predominant. Data further revealed that socially transmitted cultural messages received by young men emanated from multiple sources, such as family, peers, sexual partners, community/neighborhood, and the broader society. Race‐specific cultural messages and experiences should be addressed in interventions for this population, and programs should assist young men in developing a critical consciousness regarding these messages and experiences in order to promote health and well‐being.